Kontribusi Koperasi terhadap Pemberdayaan Ekonomi dan Kesejahteraan Masyarakat di Kota Medan (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Cooperatives play a crucial role in improving community welfare through economic empowerment, particularly in urban areas with significant socio-economic disparities, such as Medan. This study aims to analyze the contribution of cooperatives to empowering the community economy and improving the welfare of their members. A qualitative approach was used, collecting data through interviews, observations, and documentation studies at several active cooperatives in Medan. The results indicate that cooperatives play a key role in providing access to capital, entrepreneurship training, and developing micro, small, and medium enterprises (MSMEs), thereby enhancing members' economic capabilities and encouraging active participation in local economic activities. Additionally, cooperatives help foster a sense of community and mutual support, creating sustainable economic opportunities for individuals and families. This study highlights the importance of cooperatives in fostering economic independence and social cohesion in Medan. The findings provide important implications for strengthening cooperative policies, improving management practices, and refining community economic empowerment strategies in Medan to achieve long-term growth and prosperity.